LES VARIATIONS THERMIQUES SAISONNIERS ET LEURS IMPACTS SUR LE COMPORTEMENT Ã‰COPHYSIOLOGIQUES DES SEMIS DE PIN Dâ€™ALEP - Laala, Ahmed; Rached-Kanouni, Malika; Alatou, Djamel (European Scientific Journal, ESJ, 2013)
In Algeria, the pine forests are concentrated mainly in arid and semi arid regions where the climatic conditions severely limit the production potential seriously, thus the mechanism of tolerance is the most effective strategy in situations of severe and prolonged stress. In this context, our study is to determine specifically the effect of seasonal temperature variations on Aleppo pine seedlings from biochemical markers such as the synthesis of proline, soluble sugars and chlorophyll. The results reveal a very significant accumulation of proline in aerial parts than in root during the summer and winter. Thus the accumulation of various osmolytes show that Aleppo pine stands as the most species-rich carbohydrates in winter and less rich in summer. Parallel to the accumulation of these solutes, a gradual decline of chlorophyll pigment content was recorded in winter and summer. In conclusion, the study reveals the thermophilic Aleppo pine and also shows that the solutes accumulated mark well the thermal limit of this species.